2018
DOI: 10.1111/1440-1681.12902
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of regulatory T cell function in patients with delayed fracture healing

Abstract: Bone fracture healing is a multistage regenerative process that requires the collaboration of various cell types, with approximately 5%-10% of fractures not healing properly. Accumulating evidence suggests that dysregulations in the immune system are associated with defective healing. In a cohort of 30 bone fracture patients between 50 and 62 years of age, 8 patients displayed delayed healing. Compared to the 22 normal healing patients, these 8 delayed healing patients presented significantly lower frequencies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…An increasing amount of data are available about fracture healing that might be relevant in this context. 8,12,18,21 Both tendon and bone shafts need to have mesenchymal cells recruited to the site of injury from the peritendineum or the periosteum and activated. The initial inflammation is important for this process, similar in bone and tendon healing.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing amount of data are available about fracture healing that might be relevant in this context. 8,12,18,21 Both tendon and bone shafts need to have mesenchymal cells recruited to the site of injury from the peritendineum or the periosteum and activated. The initial inflammation is important for this process, similar in bone and tendon healing.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found that the rate of fracture nonunion in HIV patients is significantly higher than that in normal people [46,47]. Jiang et al [48] reported that the proportion of Treg cells in patients with a nonunion fracture was significantly lower than that in patients with a normal union fracture. Further studies have shown that the Treg cell secretory function was significantly decreased in patients with nonunion fractures.…”
mentioning
confidence: 99%
“…Hence, bone-resorbing osteoclast formation may be favored in these patients, suggesting a possible mechanism for delayed bone healing[ 182 ]. Another study supported the findings that multiple reductions in Tregs function in delayed healing patients could produce long-lasting consequences in the bone fracture healing process[ 183 ].…”
Section: Role Of the Adaptive Immune Response In Fracture Healingmentioning
confidence: 54%